The Sexual Grooming Scale – Victim Version: The Development and Pilot Testing of a Measure to Assess the Nature and Extent of Child Sexual Grooming - Winters, Georgia M. (Victims & offenders, 2022)
Sexual grooming has been deemed an integral component of child sexual abuse (CSA). However, the nature and extent of sexual grooming remains understudied in large part because an empirically-validated scale for child sexual grooming has yet to be developed. We developed the Sexual Grooming Scale – Victim Version (SGS-V) to assess the stages and behaviors described in the content-validated Sexual Grooming Model from a victim’s perspective. The SGS-V was pilot tested with 115 adult victims of CSA. Overall, results supported the feasibility in terms of implementation and its limited-efficacy. The implications for prevention, investigation, treatment, and research are discussed.